Student financial planning application (SABE) / Nurul Izzah Zainal ... [et al.] - Zainal, Nurul Izzah; Nikrul Tarmizi, Nurul Iman; Jamaluddin, Nur Anis Najwa; Zaini, Nadzirah Wafaa; Mahmud, Nurazree (Universiti Teknologi MARA, Kedah, 2023)
This project aims to create an innovation idea to solve problems in financial planning occurring in students’ real-life situations, hence we make an application for students using the name SABE. The word "save better" is reflected in the name SABE. The problem is that, due to their expensive lifestyles, students sometimes waste their money on things that are not necessary to sustain their way of life. Primarily, the objective of the app is to help students make their own budget and monitor inflow and outflow of funds, such as tracking monthly expenses, planning for savings, and the ease of controlling or managing their finances. Other than that, the tracking information helps the students control their daily expenses so they do not exceed their target. When compared to other apps, ours is different because it consists of tracking monthly or weekly expenses, and we reinvented it to provide a signal if users are overspending, a comic or reading section that can acknowledge users, and an investing section for students. The potential to help students make informed decisions and prevent financial stress by monitoring their financial health via a financial planner has numerous positive effects on society. Additionally, it is simpler to save funds more wisely. When using a personal finance management mobile app, students can examine their incoming and outgoing cash at any time and they remain visible. Students can monitor their spending and get tips for ways to save more money by using tools. We also collaborate with all the banks that most students use and for the investment section, we will probably collaborate with Tabung Haji, ASB and many more. Thus, we developed this app to help students save more money and boost their pocket money.